Estimating the global and regional burden of lower respiratory infections attributable to leading pathogens and the protective effectiveness of immunization programs - Xiaoran Yu; Huan Wang; Sheng Ma; Wanning Chen; Lin Sun; Zhiyong Zou (International Journal of Infectious Diseases)
Objectives: Reducing mortality from infectious diseases is an urgent global public health priority. Streptococcus pneumoniae, H. influenzae, and influenza virus are the three leading causes of lower respiratory infections (LRIs) death worldwide. Our objective was to assess the global burden of LRIs attributable to S. pneumoniae, H. influenzae, and influenza virus and explore the protective effectiveness of immunization programs. Methods: Data were retrieved from the Global Burden of Disease Study 2021 and World Health Organization United Nations Children's Fund Estimates of National Immunization Coverage. Locally weighted linear regression and Spearman correlation analysis were used to examine the associations between LRI mortality and vaccination coverage. Mixed-effects regression models were used to estimate the reduction in deaths that would be reduced by pneumococcal conjugate vaccine (PCV) and the H. influenzae type b (Hib) vaccine if all countries realized the Immunization Agenda 2030 (IA2030). Results: In 2021, about 30.2% of the 2.18 million LRI-related deaths were attributed to three studied pathogens. From 1990 to 2021, the age-standardized mortality rate of LRIs was attributable to three pathogens decreased by more than half. In 2022, the global vaccination rates for PCV and Hib vaccines were 60.0% and 76.0%, respectively. The LRIs attributable to S. pneumoniae (rs = −0.45, P <0.001) and H. influenzae (rs = −0.47, P <0.001) decreased with the increasing vaccination coverage of PCV and Hib. By 2030, approximately 59.9% and 70.8% of countries worldwide will reach the IA2030 targets of 90% coverage for PCV and Hib, respectively. By that time, the number of deaths from LRIs in children attributable to S. pneumoniae and H. influenzae will decrease by 54.8% and 24.4%, respectively. Conclusions: Despite the declines in LRI mortality attributed to respiratory pathogens, substantial deaths still occurred in 2021. To advance toward achieving the IA2030 targets and further mitigate mortality associated with LRIs, intensified efforts by the international community and national health systems are imperative.